A Juridical Analysis of Criminal Law and Administrative Law in Corruption Cases from a Critical Legal Studies Perspective: Analisis Yuridis Hukum Pidana dan Hukum Administrasi Dalam Perkara Tindak Pidana Korupsi Perspektif Critical Legal Studies - Atqo Darmawan Aji (Lex Renaissance, 2024)
Law enforcement of corruption against officials who harm the state often causes problems. Such conditions result in fear of state administrators to make policies. There is a dualism of regulations regarding the assessment of elements of abuse of authority, namely in the Corruption Eradication Law and the State Administration Law. Such conditions violate the principle of legal certainty. To see which legal domain is more relevant, a critical legal studies perspective is used. Critical legal studies see that law must be in line with human development and the law itself. This study uses normative research methods. The urgency of the study is to determine the views of critical legal studies in enforcing the law on corruption. The formulation of the problem in this study is to determine how to apply critical legal studies in enforcing the law on corruption. Based on critical legal studies, the form of abuse of authority is more appropriately proven first based on the provisions in the State Administration Law. Abuse of authority is more about a person's disobedience to the general principles of good government (AAUPB). The element of abuse of authority in criminal law must begin with an inner intention to commit an unlawful act, this element must be contrary to authority. Unlawful elements that conflict with authority can only be categorized as a criminal act of corruption as regulated in Article 3 of the Corruption Eradication Law. In the provisions of Article 3, the elements of self-benefit and causing state losses must also be met. The occurrence of such losses must be caused by the abuse of authority that is against the law. Therefore, not all cases of abuse of authority by state administrators must be categorized as criminal acts of corruption.Keywords: Administrative Law, Criminal Law, Corruption, Abuse of Authority AbstrakPenegakan hukum korupsi terhadap pejabat yang merugikan negara kerap kali menimbulkan permasalahan. Kondisi yang demikian mengakibatkan rasa takut dari penyelenggara negara untuk membuat kebijakan. Adanya dualisme pengaturan mengenai penilaian unsur penyalahgunaan wewenang yaitu berada di Undang-Undang Pemberantasan Tindak Pidana Korupsi dan Undang-Undang Administrasi Pemerintah. Kondisi yang demikian melanggar asas kepastian hukum. Untuk melihat domaian hukum mana yang lebih relevan maka mengunakan sudut pandang critical legal studies. Crital legal studies melihat hukum harus sejalan dengan perkembangan manusia dan hukum itu sendiri. Penelitian ini mengunakan metode penelitian normatif. Urgensi dari penelitian adalah untuk mengetahui padangan critigal legal studis dalam penegakan hukum tindak pidana korupsi. Rumusan masalah dalam penelitian ini adalah bagaimana penerapan critical legal studies dalam penegakan hukum dalam tindak pidana korupsi? Berdasarkan critical legal setudies bentuk penyalahgunaan wewenang lebih tepat dibuktikan terlebih dahulu berdasarkan ketentuan yang ada dalam UU Administrasi Pemerintah. Penyalahgunaan wewenang lebih kepada ketidakpatuhan seseorang terhadap AAUPB. Unsur penyalahgunaan wewenang dalam hukum pidana harus dimulai dengan niat batin untuk melakukan perbuatan melawan hukum, unsur tersebut harus bertentangan dengan kewenangan. Unsur melawan hukum yang bertentangan dengan kewenangan tersebut baru dapat dikategorikan sebagai tindak pidana korupsi sebagaimana diatur dalam Pasal 3 Undang-Undang Pemberantasan Tindak Pidana Korupsi.  Dalam ketentuan Pasal 3 tersebut juga harus memenuhi unsur menguntungkan diri sendiri dan mengakibatkan kerugian negara. Timbulnya kerugian tersebut harus disebabkan oleh adanya penyalahgunaan wewenang yang melawan hukum. Oleh sebab itu, tidak semua kasus penyalahgunaan wewenang oleh penyelengara negara masuk kategori tindak pidana korupsi.Kata Kunci: Hukum Admintrasi, Hukum Pidana, Korupsi, Penyalahgunaan wewenang